The role of learning disability nurses in promoting cervical screening uptake in women with intellectual disabilities: a qualitative study - Lloyd, Jennifer L.; Coulson, Neil S. (SAGE, 2014)
Research suggests that the uptake of cervical screening by women with intellectual disabilities (commonly known as learning disabilities within UK policy frameworks, practice areas and health services) is poor compared to women without intellectual disabilities. The present study explored learning disability nurses' experiences of supporting women with intellectual disabilities to access cervical screening in order to examine their role in promoting attendance and elucidate potential barriers and facilitators to uptake. Ten participants recruited from a specialist learning disability service completed a semi-structured interview and data were analysed using experiential thematic analysis. Identified individual barriers included limited health literacy, negative attitudes and beliefs and competing demands; barriers attributed to primary care professionals included time pressures, limited exposure to people with intellectual disabilities and lack of appropriate knowledge, attitudes and skills. Attendance at cervical screening was facilitated by prolonged preparation work undertaken by learning disability nurses, helpful clinical behaviours in the primary care context and effective joint working.